Effectiveness of Pocket Books to Increase Mothers’ Knowledge and Ability About Baby Massage - Primasari, Nina; Yulita, Erika; Sari, Gita Nirmala; Pipitcahyani, Tatarini Ika; Nisa, Fajriatun (Women, Midwives and Midwifery, 2025)
Background: Massage in children has been recognized as an effective method to stimulate growth due to its impact on neurochemical processes. One of the primary mechanisms involved is the stimulation of beta-endorphin, a neurochemical that plays a crucial role in increasing the amount and activation of the enzyme ornithine decarboxylase (ODC) in tissues. This enzyme is essential for cell growth and differentiation, contributing to optimal development in infants. Additionally, massage promotes the release of other growth hormones, further supporting physical and neurological development. Baby massage is performed through gentle rubs on the skin's surface, which not only enhances growth but also provides comfort, improves circulation, and strengthens the emotional bond between mother and baby. Purpose: This study aimed to assess the effectiveness of providing pocketbooks as an educational tool to enhance maternal knowledge and ability in performing baby massage. By improving maternal skills and awareness regarding baby massage techniques, this intervention sought to maximize the potential benefits of baby massage in infant development. Methods: This study utilized a quantitative approach with a quasi-experimental design, specifically employing a non-equivalent control group research method. The research was conducted at Rini Hartini’s Midwife Practice Place and involved a total of 34 respondents selected through purposive sampling. The respondents were divided into an intervention group and a control group. The intervention group received educational pocketbooks and was assessed on their knowledge and ability to perform baby massage before and after the intervention. Data collection was carried out using structured questionnaires and a skills checklist to measure both knowledge and practical ability. Results: The findings revealed a significant improvement in maternal knowledge and ability in the intervention group compared to the control group. Pre-test and post-test assessments demonstrated a statistically significant difference in the scores, with a p-value of 0.000 (<0.05). This indicates that the intervention, in the form of providing pocketbooks, had a positive effect on increasing maternal competence in baby massage. Conclusion: Based on the results, it can be concluded that the provision of pocketbooks as an educational tool effectively enhances maternal knowledge and practical skills in performing baby massage. The study findings highlight the importance of accessible educational resources in improving maternal childcare practices. The outcomes of this research are expected to contribute to further studies and interventions aimed at optimizing infant growth and development through informed parental involvement. The research findings have been published in accredited national journals, ensuring the dissemination of valuable knowledge to a broader audience in the medical and child health sectors.